The control of Cydia pomonella (L.) (Lepidoptera, Tortricidae) population using sugars under semi-arid climate (Batna, Algeria) - ZAABOUBI, Siham; BRAHIM, Imene; BRAHIM, Iness; NACER, Salah Neghmouche; MOUSSAOUI, Younes (Studia Universitatis Babeș-Bolyai Biologia, 2025)
The codling moth remains the main pest of apples in the Batna region of Algeria and causes heavy damage to apple orchards. This paper aims to show the possibility of using insecticide (Thiacloprid which may provide selective control tools) and sugar (which may induce multiple systemic resistances) to control Cydia pomonella. The field trials were carried out on the “Anna” apple tree cultivar in Tilatou (Batna, Algeria). The efficacy of sucrose and fructose (100 ppm), in comparison to Thiacloprid (25 mL ha-1), was assessed based on the proportion of fruits that larvae destroyed, the quantity of larvae gathered in corrugated cardboard, and the quantity of male moths trapped in pheromone traps. This study showed that all tested products reduced fruits damaged by Cydia pomonella. Treatments by sucrose and fructose provide percentages of damaged fruits at rates of 8.44±0.64 and 7.57±1.25, respectively, vs. 36.35±3.00 for untreated trees. The treatments also affected the number of larvae caught in bands of corrugated cardboard. Foliar spraying in the morning with sugar (every 20 days) can be an alternative method to manage the codling moth population. The use of sugars is a novel method in the plant protection strategy. These results constitute an interesting alternative to classical approaches offered by the opportunity to reduce the rate of chemical insecticides required for effective pest management. Article history: Received 30 August 2024; Revised 2 April 2025; Accepted 26 May 2025; Available online 25 June 2025